Studi Pengembangan Arah Kebijakan Penguatan Kegiatan Kemahasiswaan Universitas Islam Negeri Pada Bidang Pengembangan Bakat, Minat, Penalaran Dan Kewirausahaan Mahasiswa UIN Raden Intan Lampung - Anwar, syaiful; El- Fiah, Rifda (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to (i) Obtain the direction of the policy of strengthening student activities in the fields of developing talent, interest, reasoning and entrepreneurship carried out at RadenIntan Lampung State Islamic University. (ii) can provide direction for the development of ealistic policies in order to strengthen student activity programs in the areas of talent development, interest, reasoning and entrepreneurship at Raden Intan Lampung UIN. (iii) How do the academics and institutions of Raden Intan Lampung UIN view the development of the direction of the policy of strengthening student activities in the fields of developing talents, interests, reasoning and entrepreneurship? The method used in this study is a customized research and development (R & D) method. Preparation of the direction of policy for strengthening student activities in the field of reasoning. In the second year Limited Piloting and Evaluation will be conducted, while in the same year Piloting and Evaluation Extensions will also be conducted. The results of this study are (i) The problem of funding student development programs especially in the field of student reasoning has been considered to have received less serious attention so that it has an impact on the achievement of the students who follow the reasoning field development program, which is very minimal and often not involved the arena of competition in the field of reasoning. (ii) The direction of the policy of strengthening student activities in the field of developing talents, interests, reasoning and student entrepreneurship that UIN needs to run is involving students in lecturer research, developing student entrepreneurship programs, linking PKM activities with Real Work Lectures (KKN), forming special teams related strengthening student reasoning, strengthening the annual routine agenda program of reasoning activities, as well as developing student talent, interests, reasoning and entrepreneurship programs that cover the PKM, scientific work, seminars, arts and culture, sports c and other similar activities.